1997
DOI: 10.1007/s001340050469
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurement of cardiac output: whole-body impedance cardiography in simultaneous comparison with thermodilution and direct oxygen Fick methods

Abstract: There was close agreement between the results of the three methods in the measurement of CO. In sedated preoperative patients the accuracy of ICGWB is within clinically acceptable limits and its repeatability is excellent. ICGWB provides a useful alternative to the TD and Fick methods in cases where the pressures supplied by the pulmonary artery catheter are not essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
83
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 28 publications
10
83
0
1
Order By: Relevance
“…Whole-body impedance cardiography (CircMon R , JR Medical Ltd., Tallinn, Estonia), based on the changes in electrical impedance of the body during cardiac cycle, was used to determine beat-to beat heart rate, stroke volume, cardiac index, extracellular volume, and pulse wave velocity (PWV) [16]. Systemic vascular resistance index was calculated from radial blood pressure and cardiac index [17].…”
Section: Methodsmentioning
confidence: 99%
“…Whole-body impedance cardiography (CircMon R , JR Medical Ltd., Tallinn, Estonia), based on the changes in electrical impedance of the body during cardiac cycle, was used to determine beat-to beat heart rate, stroke volume, cardiac index, extracellular volume, and pulse wave velocity (PWV) [16]. Systemic vascular resistance index was calculated from radial blood pressure and cardiac index [17].…”
Section: Methodsmentioning
confidence: 99%
“…Comparison with thermodilution (TD) and direct Fick methods showed that ICG WB measures CO accurately in different conditions (in the supine position, during head-up tilt, after the induction of anesthesia and after coronary artery bypass surgery) (14,27,28). The differences in CO values between ICG WB and TD were comparable with those attained between direct Fick and TD, and the repeatability of ICG WB was nearly twice as good as in TD (27,28). Therefore, ICG WB is an adequate method to estimate CO and its changes.…”
Section: Discussionmentioning
confidence: 99%
“…The bias and limits of agreement between thermodilution and ICG WB were 0.00 l/min ± 1.37 l/min and between the Fick method and ICG WB were −0.32 l/min ± 1.92 l/min, respectively. The repeatability value for ICG WB was excellent (0.57 l/min) (26).…”
Section: Methodsmentioning
confidence: 98%